Laminated Jute and Glass Fibre Reinforced Composite for Repairing Concrete Through Wrapping Technique - Amirhafizan, M.H.; Yuhazri, M.Y.; Umarfaruq, H.M.; Lau , S. T. W.; Kamarul, A.M.; Zulfikar, A.J. (International Journal of Integrated Engineering, 2023)
In the recent decades, the research of natural fibre in concrete structure materials had attracted many researchers and engineers due to its good agreement in mechanical properties, economically and sustainability. In this study, the jute and glass fibre laminated composite for repairing concrete through the wrapping technique was analysed. A total of 66 concrete specimens, 150 x 50 mm each, were tested. Six concrete specimens were kept as control specimen, 30 specimens were laminated with glass fibre-reinforced thermoset (GFRT) and 30 specimens were laminated with jute fibre-reinforced thermoset (JFRT). The vinyl ester (VE) was used as a matrix. Eventually, all specimen was tested using compression and Brazilian testing. It was found that both GFRT and JFRT had the potential to improve the mechanical performance of concrete specimens with the increment of a maximum number of five (5) layers of woven fibre. It was also found that the four (4) layers of JFRT had the highest mechanical properties with improvement of 72.62% compare to GFRT (4 layers). The results presented here may facilitate improvements in the concrete specimen by using JFRT where it had been suggested to have a higher improvement for the concrete specimen with the optimum layers applied. Hence, jute fibre had been proven to have better performance and can replace the use of glass fibre.